STRUKTUR ANATOMI SEBELAS JENIS KAYU DARI JAWA BARAT - Sri Rulliaty (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Anatomical featuru of eleoen wood species from West Java were examined and compared for identification purposes. The reaul'tll show that each wood species ean be diBtinguished one from the other. All fibers N'ptate is one chanu:temtic features of family Bwwraceae. Tile celll pterospermum types distinguished Planchonia valida Bl. from others Species.Lit.sea rmna Hook. has oil cellB, one of characteristic features of family Lauraceae.